1995
DOI: 10.1002/j.1460-2075.1995.tb00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum-to-cytosol transport of free polymannose oligosaccharides in permeabilized HepG2 cells.

Abstract: Free polymannose oligosaccharides have recently been localized to both the vesicular and cytosolic compartments of HepG2 cells. Here we investigated the possibility that free oligosaccharides originating in the lumen of the endoplasmic reticulum (ER) are transported directly into the cystosol. Incubation of permeabilized cells in the absence of ATP at 37 degrees C led to the intravesicular accumulation of free Man9GlcNAc2 which was generated from dolichol‐linked oligosaccharide in the ER. This oligosaccharide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
85
0
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 38 publications
10
85
0
1
Order By: Relevance
“…Although the sequential processing events of free OSs have been well characterized (15)(16)(17)(18)(19), the molecular nature of the enzyme͞transporters involved in this process has not been identified, with the exception of cytosolic PNGase (35). Because free OSs in the lumen of the ER can potentially interfere with the glycan-dependent protein quality control system in the ER (2-4), the rapid clearance of them from the lumen of the ER may be of great importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the sequential processing events of free OSs have been well characterized (15)(16)(17)(18)(19), the molecular nature of the enzyme͞transporters involved in this process has not been identified, with the exception of cytosolic PNGase (35). Because free OSs in the lumen of the ER can potentially interfere with the glycan-dependent protein quality control system in the ER (2-4), the rapid clearance of them from the lumen of the ER may be of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been found that, during the N-glycosylation of proteins in the ER, a significant number of unconjugated, free oligosaccharides (free OSs) are formed (7)(8)(9). The occurrence of free OSs has been reported in a wide variety of cells (10)(11)(12)(13)(14), and their sequential processing event of free OSs in mammalian cells has also been well characterized (15)(16)(17)(18)(19). When the free OSs are formed in the lumen of the ER, they are transported out of the ER to the cytosol (15).…”
mentioning
confidence: 99%
“…Under these conditions there is no transfer of oligosaccharide from LLO onto protein (43), and after these brief 10-min incubations less than 10% of the LLO fraction is lost (probably as free oligosaccharides (43)). After permeabilization, LLO in both the patient's and normal cells are found to be partially deglucosylated so that in both cases Man 9 GlcNAc 2 -PP-dolichyl is a major species.…”
Section: Glc 1 Man 9 Glcnac 2 -Pp-dolichyl Accumulates Upon Treatmentmentioning
confidence: 99%
“…Flavivirus infection of mammalian cells, for example, causes a general increase in peptide concentration in the ER and thus leads to increased presentation of cellular instead of viral antigens at the cell surface (7). In addition, removal of peptides from the secretory pathway at an early stage is essential to prevent competition with secretory proteins for covalent modifications in the ER and Golgi apparatus; nonspecific peptides in the secretory pathway would also compete with binding of peptides derived from extracellular antigens to the MHC class II complex in a late compartment of the secretory pathway (8,9). Finally, uncontrolled release of nonspecific peptides into the extracellular space would interfere with intercellular communication mediated by neuropeptides or peptide pheromones (10).…”
mentioning
confidence: 99%
“…In contrast to secretory proteins, however, glycopeptides are not packaged into ER-toGolgi transport vesicles; instead, they are transported directly across the ER membrane to the cytosol in an ATP-and cytosol-dependent fashion (11). Most TAP substrates and free polymannose oligosaccharides are also efficiently transported from the ER lumen to the cytosol in an ATP-dependent fashion (5,6,8). Initially, retrograde transport across the ER membrane was assumed to be restricted to small molecules and was viewed as a disposal pathway for end products of ''ER degradation'' of misfolded secretory proteins (11).…”
mentioning
confidence: 99%